Ukrainian feminism as a factor of social changes - Ярослав Пасько; Ірина Зайцева (Cхід, 2023)
The article discusses the theoretical foundations of Ukrainian feminism, substantiates its practical significance for social changes in society. The subject of research attention is the individual and collective dimensions of feminism, the influence of this important social phenomenon on the value evolution of Ukrainian society. Attention is focused on the goal-rational and value-rational dimensions of the women's community, its moral and normative foundations. The role of the Ukrainian lifeworld in the value demarcation of Ukrainian women from imperial sociality is understood.